Intranasal Polymeric and Lipid-Based Nanocarriers for CNS Drug Delivery - Rebecca Maher; Almudena Moreno-Borrallo; Dhruvi Jindal; Binh T. Mai; Eduardo Ruiz-Hernandez; Andrew Harkin (MDPI AG, 2023)
Nanomedicine is currently focused on the design and development of nanocarriers that enhance drug delivery to the brain to address unmet clinical needs for treating neuropsychiatric disorders and neurological diseases. Polymer and lipid-based drug carriers are advantageous for delivery to the central nervous system (CNS) due to their safety profiles, drug-loading capacity, and controlled-release properties. Polymer and lipid-based nanoparticles (NPs) are reported to penetrate the blood-brain barrier (BBB) and have been extensively assessed in in vitro and animal models of glioblastoma, epilepsy, and neurodegenerative disease. Since approval by the Food and Drug Administration (FDA) of intranasal esketamine for treatment of major depressive disorder, intranasal administration has emerged as an attractive route to bypass the BBB for drug delivery to the CNS. NPs can be specifically designed for intranasal administration by tailoring their size and coating with mucoadhesive agents or other moieties that promote transport across the nasal mucosa. In this review, unique characteristics of polymeric and lipid-based nanocarriers desirable for drug delivery to the brain are explored in addition to their potential for drug repurposing for the treatment of CNS disorders. Progress in intranasal drug delivery using polymeric and lipid-based nanostructures for the development of treatments of various neurological diseases are also described.